2011
DOI: 10.1002/app.34354
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maintaining temperature and time on properties and structures of poly(dimethyldiallylammonium chloride)

Abstract: Effects of maintaining temperature (T3) and time (t) on properties and structures of product poly(dimethyldiallylammonium chloride) (PDMDAAC) are researched in this article. The results showed that higher the T3 shorter the time t needed for polymer products' intrinsic viscosity ([η]) and monomer conversion (Conv.) to reach their maximum values. The maximum [η] was 4.69 dL g−1 and corresponding Conv. was 100.00%, when t = 96 h and T3 = 55°C. The reaction phenomena and products' FTIR and NMR spectra indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The results in Table 4 showed that the contents of these impurities in DADMAC samples were different from each other. The molecular weights (calculated by intrinsic viscosity [ η ]) of poly-DADMACs changed with the variation of the sorts of impurities and their contents even under the same optimum polymerization condition [14], so that it could further not only prove the obvious effect of the impurities on the molecular weight of polymer products, but also illustrate the importance to establish a product quality standard for promoting the overall level of the DADMAC production in industry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results in Table 4 showed that the contents of these impurities in DADMAC samples were different from each other. The molecular weights (calculated by intrinsic viscosity [ η ]) of poly-DADMACs changed with the variation of the sorts of impurities and their contents even under the same optimum polymerization condition [14], so that it could further not only prove the obvious effect of the impurities on the molecular weight of polymer products, but also illustrate the importance to establish a product quality standard for promoting the overall level of the DADMAC production in industry.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the research on the products with high and serial molecular weight or the products with controlled molecular weight distribution is always the key point [14]. However, for DADMAC-based polymers formed from radical polymerization, the species, and amounts of impurities in DADMAC monomer solution have been considered to be one of the key influencing factors on the polymerization and product molecular weights, in addition to the polymerization technology [15], the sorts and amounts of initiators [16], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The specific preparation conditions of PDADMAC are listed in Supporting Information Table S1. Compared with previous studies, the preparation of high SCD PDADAMC required lower temperature and more initiators (Jia & Zhang, 2010, 2012.…”
Section: Preparation and Characterization Of Pdadmacmentioning
confidence: 86%
“…In order to investigate the effect of PDADMAC with different SCD values on flocculation process, the PDADMAC samples with different SCD values were prepared by adjusting temperature and time of reaction, and mass ratio of initiator and promoter in the reaction solution. The preparation reaction of PDADMAC was a typical free radical polymerization (Jia & Zhang, ). The DADMAC monomer solution was placed into polymerization apparatus with thermometer and water bath.…”
Section: Methodsmentioning
confidence: 99%
“…Practical importance of DADMAC homopolymer and copolymer studies involving polymerization mechanism and kinetics, molecular characterization, and solution properties of this system have drawn great interest. Highly hygroscopic nature of PDADMAC causes difficulties in characterization polymerization reaction by chemical methods or isolation and gravimetrically . The electrostatic repulsion between the ion and the charged macroradical depend on the pH value of the medium and the concentrations of ionic species.…”
Section: Introductionmentioning
confidence: 99%